Hernia Inguinalis Permagna: Laporan Kasus - Yusmaidi; Wasiatul Ilma (Medula, 2021)
Introduction: Giant inguinal hernia is a rare form of hernia, generally defined as an inguinal hernia those size extends below the midpoint of the inner thigh when standing. The management of this type of hernia uses surgical methods with various techniques. This type of hernia is classified as difficult because it requires returning the contents of the hernia bag into the abdominal cavity which is usually empty so that it can cause intra-abdominal hypertension and compartments syndrome of abdominal. Case: A 90 year old man presented with a complaint of a large lump in the right groin. Other complaints do not exist. Management in this patient was a herniotomy continued with strengthening of inguinal canal trough Bassini technique followed by the McVay procedure. Discussion: There is a classification of this type of hernia. Surgical techniques that can be performed to treat giant inguinal hernia also vary. Conclusion: Giant inguinal hernia is a rare case, requires proper management so that mortality and morbidity do not increase.